Marketing public relations {MPR) - Charmaine Scriven Charmaine Scriven (Communicare)
This article addresses the Marketing Public Relations (MPR) concept, whose emergence can partly be ascribed to the continuous debate regarding the respective boundaries of both the fields of public relations and marketing. The article first explains the nature of the debate and then explores the emergence and some theory of MPR. It also argues the position of MPR in the organisation and finally contemplates its future. This article in particular debates the current apprehension that MPR is merely product publicity or mostly adds credibility to an organisation's product advertising efforts. It argues that MPR can achieve much more in the organisation than scholars and theorists currently address, especially with regard to the establishment of long-term customer relationships and trust.